Chapter Introduzione - Mastronardi, Luigi (Studi e saggi, 2020)
The present chapter introduces the concepts and the issues about Italian inner areas, as defined by the Strategia nazionale per le Aree Interne (National Strategy for Inner Areas - SNAI). In particular, it focuses on a new enterprise model called Community-based cooperatives; they play a fundamental role in the regional development process, from economic, social and environmental points of view. Finally, the key elements of these new cooperatives are highlighted.